Prospective Tracking of Donor-Reactive T-Cell Clones in the Circulation and Rejecting Human Kidney Allografts - Aschauer, Constantin; Jelencsics, Kira; Hu, Karin; Heinzel, Andreas; Gregorich, Mariella Gloria; Vetter, Julia; Schaller, Susanne; Winkler, Stephan M.; Weinberger, Johannes; Pimenov, Lisabeth; Gualdoni, Guido A.; Eder, Michael; et al. (Frontiers in Immunology, 2021)
Background Antigen recognition of allo-peptides and HLA molecules leads to the activation of donor -reactive T-cells following transplantation, potentially causing T-cell mediated rejection (TCMR). Sequencing of the T-cell receptor (TCR) repertoire can be used to track the donor-reactive repertoire in blood and tissue of patients after kidney transplantation. Methods/Design In this prospective cohort study 117 non-sensitized kidney transplant recipients with anti-CD25 induction were included. Peripheral mononuclear cells (PBMCs) were sampled pre-transplant and at the time of protocol or indication biopsies together with graft tissue. Next generation sequencing (NGS) of the CDR3 region of the TCRbeta chain was performed after donor stimulation in mixed lymphocyte reactions to define the donor-reactive TCR repertoire. Blood and tissue of six patients experiencing a TCMR and six patients without rejection on protocol biopsies were interrogated for these TCRs. To elucidate common features of T-cell clonotypes a network analysis of the TCR repertoires was performed. Results After transplantation the frequency of circulating donor-reactive CD4 T-cells increased significantly from 0.86±0.40% to 2.06±0.40% of all CD4 cells (p<0.001, Mean dif.: -1.197, CI: -1.802, -0.593). The number of circulating donor-reactive CD4 clonotypes increased from 0.72±0.33% to 1.89±0.33% (p<0.001, Mean dif.: -1.168, CI: -1.724, -0.612). No difference in the percentage of donor-reactive T-cells in the circulation at transplant biopsy was found between subjects experiencing a TCMR and the control group (p=0.64 (CD4+), p=0.52 (CD8+)). Graft infiltrating T-cells showed an up to six-fold increase of donor-reactive T-cell clonotypes compared to the blood at the same time (3.7 vs. 0.6% and 2.4 vs. 1.5%) but the infiltrating TCR repertoire was not reflected by the composition of the circulating TCR repertoire despite some overlap. Network analysis showed a distinct segregation of the donor-reactive repertoire with higher modularity than the overall TCR repertoire in the blood. These findings indicate an unchoreographed process of diverse T-cell clones directed against numerous non-self antigens found in the allograft. Conclusion Donor-reactive T-cells are enriched in the kidney allograft during a TCMR episode and dominant tissue clones are also found in the blood. Trial registration Clinicaltrials.gov: NCT: 03422224 (https://clinicaltrials.gov/ct2/show/NCT03422224)